Borderline states: a topography of contemporary psyche - Ancona de Faria, Alvaro (Journal of analytical psychology, 2022)
This paper presents a discussion of issues concerning the concept of borderline personality disorder. We start from the constitution of the borderline structure, and move towards understanding particular aspects of borderline development, both on an individual and a collective level. This discussion is based on the examination of a progression in three different concentric circles: first, the context of child‐parent relationships; second, interpersonal relationships established in the school environment; and, finally, an amplification of some aspects of contemporary culture that could be related to the current importance of this condition. Cet article présente une discussion sur les questions relatives au concept de trouble de la personnalité borderline. Nous partons de la constitution de la structure borderline, pour aller ensuite vers la compréhension d'aspects particuliers du développement borderline, à la fois au niveau individuel et collectif. La discussion est fondée sur l'étude d'une progression dans trois cercles concentriques différents: premièrement le contexte des relations enfant‐parent, deuxièmement les relations interpersonnelles établies dans l'environnement scolaire, et en dernier une amplification de certains aspects de la culture contemporaine qui pourraient rendre compte de l'importance actuelle de ce trouble. In diesem Beitrag werden Fragen zum Konzept der Borderline‐Persönlichkeitsstörung diskutiert. Wir beginnen bei der Konstitution der Borderline‐Struktur und nähern uns dem Verständnis bestimmter Aspekte der Borderline‐Entwicklung sowohl auf individueller als auch auf kollektiver Ebene. Die Diskussion basiert auf der Untersuchung einer Progression in drei verschiedenen konzentrischen Kreisen: erstens dem Kontext der Kind‐Eltern‐Beziehungen, zweitens den zwischenmenschlichen Beziehungen, die im schulischen Umfeld aufgebaut wurden und schließlich einer Amplifikation durch einige Aspekte der zeitgenössischen Kultur, die mit der aktuellen Bedeutung dieses Zustandes in Verbindung gebracht werden könnten. Questo articolo presenta una discussione su questioni relative al concetto del disturbo borderline di personalità. Partiamo dalla costituzione della struttura borderline, e ci spostiamo verso la comprensione di aspetti particolari dello sviluppo borderline, sia a livello individuale che collettivo. La discussione si basa sull'esame di una progressione in tre diversi cerchi concentrici: in primo luogo, il contesto delle relazioni bambino‐genitore, in secondo luogo, le relazione interpersonali stabilite nell'ambiente scolastico, ed infine un ampliamento di alcuni aspetti della cultura contemporanea che potrebbero essere messi in relazione con l'importanza attuale di questa condizione. В данной статье обсуждаются проблемы, связанные с концепцией пограничного расстройства личности. Вначале мы рассмотрим устройство пограничной структуры, затем перейдем к осмыслению отдельных аспектов развития пограничного расстройства, как на индивидуальном, так и на коллективном уровне. Обсуждение основывается на рассмотрении развития в различных сферах, представленных в виде трех концентрических окружностей: во‐первых, в контексте детско‐родительских отношений; во‐вторых, в межличностных отношениях, складывающихся в школьной среде; и, наконец, при амплификации к некоторым аспектам современной культуры, которые можно связать со значимостью этого состояния в настоящем. El presente trabajo presenta una discusión sobre temas que conciernen al concepto del trastorno límite de la personalidad (borderline). Comenzamos con la constitución de la estructura borderline, para luego movernos hacia la comprensión de aspectos particulares del desarrollo borderline, tanto a nivel individual como colectivo. La discusión se basa en el análisis de la progresión a través de tres círculos concéntricos: primero, el contexto de la relación parental; segundo, las relaciones interpersonales en el contexto escolar; y finalmente una amplificación de ciertos aspectos de la cultura contemporánea que podrían estar relacionados con la importancia actual de esta condición. 边缘状态:当代心理的版图 本文讨论了边缘型人格障碍概念的相关问题。我们从边缘架构的构建开始, 然后在个人和集体层面上理解边界发展的特定方面。讨论基于三个不同同心圆的发展过程来展开:第一, 亲子关系的背景；第二, 在学校环境中建立的人际关系；最后是一个放大, 针对的是当代文化中与这种状况的重要性有关的一些方面。 Este artigo apresenta uma discussão de questões relacionadas ao conceito de transtorno de personalidade limítrofe. Partimos da constituição da estrutura limítrofe e avançamos para a compreensão de aspectos particulares do desenvolvimento limítrofe, tanto em nível individual quanto coletivo. A discussão baseia‐se no exame de uma progressão em três círculos concêntricos diferentes: primeiro, o contexto das relações filho‐pai; segundo, as relações interpessoais estabelecidas no ambiente escolar; e, finalmente, uma ampliação para alguns aspectos da cultura contemporânea que poderiam estar relacionados à importância atual dessa condição.